2022
DOI: 10.31234/osf.io/gnfwa
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changes in UK Parental Mental Health Symptoms over 10 months of the COVID-19 Pandemic

Abstract: Background. The threats to health, associated restrictions, and economic consequences of the COVID-19 pandemic have been linked to increases in mental health difficulties for many. Parents, in particular, have experienced many challenges such as having to combine work with home-schooling their children and other caring responsibilities. Yet, it remains unclear how parental mental health has changed throughout the pandemic or what factors may have mitigated or compounded the impact of the pandemic on parents’ m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 18 publications
2
12
1
Order By: Relevance
“…There have been inconsistent findings considering emotional well-being over the course of the pandemic. Our results are in line with previous results showing improvement of emotional well-being among children (Achterberg et al, 2021;Skripkauskaite et al, 2020) over the course.…”
Section: Discussionsupporting
confidence: 93%
“…There have been inconsistent findings considering emotional well-being over the course of the pandemic. Our results are in line with previous results showing improvement of emotional well-being among children (Achterberg et al, 2021;Skripkauskaite et al, 2020) over the course.…”
Section: Discussionsupporting
confidence: 93%
“…This is potentially due to measurement differences as most quantitative studies measure changes in scores while qualitative ones focus on the most salient experience for the individual. Additionally, research suggests that although improvements in mental health after lockdown were observed among most young people, they did not manifest in at-risk youth 52. The latter study’s selection criterion for at-risk youth was household income, which although partially overlapping with ethnic minority, remains a distinctive non-interchangeable demographic 53.…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, research suggests that although improvements in mental health after lockdown were observed among most young people, they did not manifest in at-risk youth. 52 The latter study’s selection criterion for at-risk youth was household income, which although partially overlapping with ethnic minority, remains a distinctive non-interchangeable demographic. 53 This is not a criterion we used for our young people.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, research suggests that although improvements in mental health after lockdown were observed amongst most young people, they did not manifest in at-risk youth [48]. The latter study's selection criteria for at-risk youth was household income, which although partially overlapping with ethnic minority, remains a distinctive non-interchangeable demographic [49].…”
Section: Discussionmentioning
confidence: 99%